2012
DOI: 10.1128/jb.01765-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of “Candidatus Microthrix parvicella” Bio17-1, a Long-Chain-Fatty-Acid-Accumulating Filamentous Actinobacterium from a Biological Wastewater Treatment Plant

Abstract: f "Candidatus Microthrix" bacteria are deeply branching filamentous actinobacteria which occur at the water-air interface of biological wastewater treatment plants, where they are often responsible for foaming and bulking. Here, we report the first draft genome sequence of a strain from this genus: "Candidatus Microthrix parvicella" strain Bio17-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Preliminary details from the annotation of the M. parvicella str. Bio17-1 genome suggest the absence of a nitrite reductase (Muller et al, 2012). However, a BLAST search of this genome with the putative gene from RN1 identified a CDS with 99.9% nucleotide sequence identity.…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary details from the annotation of the M. parvicella str. Bio17-1 genome suggest the absence of a nitrite reductase (Muller et al, 2012). However, a BLAST search of this genome with the putative gene from RN1 identified a CDS with 99.9% nucleotide sequence identity.…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
“…Thus, although the discussions focus on the RN1 genome, its features and subsequent proposed metabolic model could be considered relevant generally to M. parvicella. During the review process of this manuscript, a draft genome sequence of the M. parvicella strain Bio17-1 was published (Muller et al, 2012). Genome sequence comparison of the RN1 and Bio17-1 was made using the JSpecies software (Richter and Rosselló-Móra, 2009), giving a calculated average nucleotide identity of 99% over the 89% of the genomes aligned by the programme.…”
Section: Comparison Of Central Pathways In M Parvicellamentioning
confidence: 99%
“…The Long chain fatty acid (LCFA) content in wastewater influents is a significant influencing factor promoting the growth of Candidatus M. parvicella (Dunkel et al, 2015). This organism is responsible for bulking (Martins et al, 2004;Muller et al, 2012) and might be the most frequent in bulking situations (Rossetti et al, 2005;Guo et al, 2013;Santos et al, 2015). Surprisingly, Candidatus M. parvicella was considerably abundant in the non-bulking AS (3.20%), and a previous study showed that >3% Candidatus M. parvicella in AS could cause foaming problems in WWTPs (Kaetzke et al, 2005).…”
Section: Biological and Environmental Factors Causing Sludge Bulkingmentioning
confidence: 99%
“…Therefore, the use of functional genes for multiplex PCR seems to be much easier. Recently, a genome announcement of M. parvicella has been published (Muller et al, 2012). Although the sequence assembly is not complete yet, some functional gene sequence will be soon available and the subsequent development of other quantification tools will be possible.…”
Section: Comparison Between Taqman Sybr Green and Microscopymentioning
confidence: 99%